Peningkatan Pemahaman Bahaya Merokok Siswa Melalui Media Poster dan Video di Madrasah Aliyah Miftahul Ulum Kabupaten Kubu Raya - Fazny, Bella Yugi; Nurrahmi, Hesty; ., Habibah (Counseling AS SYAMIL: Jurnal Ilmiah Bimbingan Konseling Islam, 2021)
Abstract: The purpose of this study was to determine the effectiveness of the process of implementing classical guidance services using poster and video media. The success of this study occurs when there is an increase in the understanding of the dangers of smoking in active smokers. Counseling Guidance Action Research (PTBK) was carried out in 2 cycles using questionnaires, interviews, observations and documentation. Based on the results of study, it can be concluded that the use of video media in cycle 2 is considered more effective in providing classical guidance services than the use of poster media in cycle 1. Submission material of understanding the dangers of smoking using poster in cycle 1 received a passive participation response from students. After the students finished studying the poster information, the students looked bored, and not enthusiastic until the activity ended. That contrast with cycle 2 of providing classical guidance services using the video media, students seemed to be more actively focused on listening to videos, expressing themselves during the brainstorming session. Submission of material using video is considered more effective, because it appears a decrease in the number of students experiencing boredom. The results of the evaluation of the questionnaire on the understanding of the dangers of smoking showed that before the provision of classical guidance services, the level of students' understanding of the dangers of smoking was low (mean score of 25). After cycle 1 was run using poster media, there was an increase in understanding of the dangers of smoking to a moderate level (mean score 38). Then after the researchers ran cycle 2 the provision of classical guidance services using video media, students experienced an increase in understanding the dangers of smoking to a high level (mean 60). The use of video media is considered effective and recommended in providing classical guidance services to active smoking students at Madrasah Aliyah Miftahul Ulum.